Possibility of Increasing Container Traffic in the Port of Koper Due to Introducing the Sea Motorway - Horvat, Urša (Promet - Traffic&Transportation, 2012)
The aim of this paper is to present the possibility of introducing the motorway of the sea to the Port of Koper. Based on the present situation in the Port of Koper and the planned extension of the container terminal determined by the development plans of the Port of Koper, the paper presents the increase in the container transhipment due to the introduction of the motorway of the sea and its influence on the hinterland infrastructure. For this purpose a simulation was introduced which shows the increase in container transhipment and its distribution between the road and railway part of the container terminal until the year 2015. The maximum capacity of the road and railway part of the container terminal presents two critical points which would be reached due to the introduction of the motorway of the sea to the Port of Koper. The consequence would be a change in the distribution ratio of transhipment between road and railway part of the container terminal. This would overturn the desired ratio of 30:70 (road: railway) determined by the guidelines of the White Paper. KEY WORDS: Motorway of the sea, Port of Koper, container transhipment